2009
DOI: 10.1007/s00415-009-5309-x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired pendular nystagmus in multiple sclerosis: an examiner-blind cross-over treatment study of memantine and gabapentin

Abstract: A prospective examiner-blind, cross-over study was conducted to compare the efficacy of memantine (40 or 60 mg/day) and gabapentin (1,200 mg/day) as therapy for acquired fixational pendular nystagmus (APN) in 11 patients with multiple sclerosis. APN was documented in 20 eyes by electrooculography (EOG). The primary objective of the study was an at least 50% reduction in amplitude and/or frequency of APN compared with baseline values in EOG. This aim was reached for 17 of 20 APN-affected eyes with memantine 40-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 39 publications
(35 reference statements)
2
32
1
1
Order By: Relevance
“…31 In contrast to the results of a recent study in a small group of patients, 10 Shery et al 8 found that gabapentin and memantine were both effective in treating APN secondary to MS but not to other neurologic diseases, which is in accordance with our personal clinical experience. Finally, the studies from Starck 21,32 showing improvement of APN with gabapentin and memantine only tested patients with MS.…”
Section: Resultsmentioning
confidence: 99%
“…31 In contrast to the results of a recent study in a small group of patients, 10 Shery et al 8 found that gabapentin and memantine were both effective in treating APN secondary to MS but not to other neurologic diseases, which is in accordance with our personal clinical experience. Finally, the studies from Starck 21,32 showing improvement of APN with gabapentin and memantine only tested patients with MS.…”
Section: Resultsmentioning
confidence: 99%
“…Because potassium channels are abundant on cerebellar Purkinje cells, the aminopyridines may increase their discharge. The Gabapentin (8,9,16,45,77) Memantine (8,9,33,47,77) 4-Aminopyridine (20,23) and 3,4-diaminopyridine (19,24,21) Baclofen (14,16,29,37) Clonazepam (12) Valproate (43) Trihexyphenidyl (17,18,58) Benztropine (17) Scopolamine ( (142) enhanced Purkinje cell activity could then restore normal levels of inhibition of vertical vestibular eye movements, leading to suppression of the nystagmus (22). However, 4-aminopyridine suppresses upbeat nystagmus in some patients (23), and it may occasionally cause downbeat nystagmus to convert to upbeat nystagmus (24).…”
Section: Downbeat Nystagmusmentioning
confidence: 98%
“…Standard dosage Memantine is often effective for APN and OPT at a dose of 10 mg four times daily [12•,13•,15,Class II]. In some patients with APN, complete suppression is possible with a total dose of 60 mg per day, but side effects are frequent [15,Class II].…”
Section: Memantinementioning
confidence: 99%